2018
DOI: 10.1186/s12974-018-1285-3
|View full text |Cite
|
Sign up to set email alerts
|

Microglia P2X4 receptor contributes to central sensitization following recurrent nitroglycerin stimulation

Abstract: BackgroundThe mechanism underlying migraine chronification remains unclear. Central sensitization may account for this progression. The microglia P2X4 receptor (P2X4R) plays a pivotal role in the central sensitization of inflammatory and neuropathic pain, but there is no information about P2X4R in migraine. Therefore, the aim of this study was to identify the precise role of microglia P2X4R in chronic migraine (CM).MethodsWe used an animal model with recurrent intermittent administration of nitroglycerin (NTG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 42 publications
(43 reference statements)
4
70
1
Order By: Relevance
“…Recent evidence suggests that microglia surrounding TNC neurons directly or indirectly influence the establishment of central sensitization. Previous results from our team have indicated that microglial activation was correlated with NTG-induced hypersensitivity in C57BL/6 mice and also had an effect on central sensitization induced by chronic intermittent nitroglycerin (NTG) [4]. However, the molecular mechanism that underlies the crosstalk between microglia and neurons of the TNC needs further study.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent evidence suggests that microglia surrounding TNC neurons directly or indirectly influence the establishment of central sensitization. Previous results from our team have indicated that microglial activation was correlated with NTG-induced hypersensitivity in C57BL/6 mice and also had an effect on central sensitization induced by chronic intermittent nitroglycerin (NTG) [4]. However, the molecular mechanism that underlies the crosstalk between microglia and neurons of the TNC needs further study.…”
Section: Introductionmentioning
confidence: 97%
“…However, the exact roles of activated microglia and P2X4Rs are not fully understood in migraine. In our previous studies, we found that the expression of P2X4Rs was increased in the TNC after repeated NTG stimulation [4]. P2X4Rs were associated with NTG-induced hyperalgesia and the changes in neurochemical signs accompanying migraine in the TNC, such as the signalling of c-Fos and calcitonin gene related peptide (CGRP).…”
Section: Introductionmentioning
confidence: 99%
“…The theory that purinergic signaling participats in the pathophysiology of migraine was proposed by Geoffrey Burnstock in the 1980 [20,21]. The purinergic receptors, P2 × 4R and P2Y12R, were con rmed to contribute to the pathogenesis of CM according to our previous works [16,18]. P2 × 7R, an ionotropic purinergic receptor that is widely expressed in the microglia [22,23], has been reported to be involved in the cancer pain, neuropathic pain and in ammatory pain by mediating the microglial activation and the in ammatory response [24][25][26].…”
Section: Introductionmentioning
confidence: 93%
“…The mechanical withdrawal threshold of the hind paw and periorbit was assessed every other day before and 2 hours after NTG injection. We used Von Frey laments with the up-down method to determine the withdrawal threshold to mechanical stimulation as previously described [16]. Brie y, a series of Von Frey laments (range from 0.01 g to 2 g) were applied to the hind paw or periorbit, with an initial stimulation strength of 0.4 g. If there was no response to the stimulation, the lament strength was increased; Otherwise, the lament strength was decreased until there was a positive reaction.…”
Section: Measurement Of the Mechanical Withdrawal Thresholdmentioning
confidence: 99%
See 1 more Smart Citation